Growin: Modeling ionospheric instability growth rates - Smith Jonathon M.; Klenzing Jeffrey (Journal of Space Weather and Space Climate, 2022)
Seasonal and zonal climatologies of Rayleigh–Taylor growth rates under geomagnetically quiet conditions during solar minimum and solar moderate conditions as a function of local time and altitude are calculated using open source data and software. It is under the action of the Rayleigh–Taylor instability that plumes of depleted plasma, or plasma bubbles, are understood to develop in the bottomside of the equatorial ionosphere. The growin python module utilizes other Heliophysics python modules to collate and process vertical plasma drift to drive the SAMI2 is Another Model of the Ionosphere (SAMI2) model and subsequently calculate the flux tube integrated Rayleigh–Taylor growth rate. The process is repeated for two different types of drift inputs: the Fejer–Scherliess model and measured drifts from the Communication/Navigation Outage Forecasting System (C/NOFS). These growth rates are compared to bubble occurrence frequencies obtained from a dataset of bubbles detected by the C/NOFS satellite. There is an agreement between periods of strong positive instability growth and high frequencies of bubble occurrence in both low and moderate solar activity conditions when using C/NOFS drifts. Fejer–Scherliess drifts are only in agreement with bubble occurrence frequencies during moderate solar activity conditions. Bubble occurrence frequencies are often above 25%, even when growth rates in the bottomside F region are negative. The climatological nature of the growth rates discussed here begs further study into the day-to-day variability of the growth rate and its drivers.